2014
DOI: 10.17795/ajdr-21348
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Dentists Towards Patients With HIV, Hepatitis B and Hepatitis C Infections

Abstract: Background: Dental practitioners can be exposed to the human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) during routine work. Objectives: In this study, the knowledge, attitude, and practice of the dentists in Zahedan were examined on patients with HIV, HBV, and HCV infections. Materials and Methods: This cross-sectional study was carried out on 100 dentists in Zahedan in 2013. A reliable and valid questionnaire on knowledge, attitude and performance of the dentists towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 11 publications
6
34
0
Order By: Relevance
“…The results revealed that dentists' knowledge score was less than 50%, which was in concordance with other surveys (5)(6)(7)(10)(11)(12). This may be due to insufficient training, both at universities and in retraining programs post-graduation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results revealed that dentists' knowledge score was less than 50%, which was in concordance with other surveys (5)(6)(7)(10)(11)(12). This may be due to insufficient training, both at universities and in retraining programs post-graduation.…”
Section: Discussionsupporting
confidence: 87%
“…This may be due to insufficient training, both at universities and in retraining programs post-graduation. Other (6). The current study indicates that 68.8% of respondents had a history of injury, and 29 out of 40 who worked more than six hours per day mentioned at least one injury from sharp instruments; this number was 23 for those working under six hours.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The study was conducted with the participation of 58 dentists throughout Turkey between July-August 2018 after receiving the required ethical and administrative approvals. A 33-item digital survey created using literature data [16][17][18][19] was applied. The dentists were requested to answer the survey questions individually and voluntarily.…”
Section: Methodsmentioning
confidence: 99%
“…As the knowledge of this group about the prevention and transmission of hepatitis was not high, it is predictable that they do not follow preventive strategies completely. In a study in a teaching hospital in Lahore, it was determined that lack of awareness was the commonest reason for not being vaccinated against hepatitis B [19].…”
Section: Discussionmentioning
confidence: 99%